Effect of dehumidification drying environment on surface gloss of one component waterborne wood top coating. (5th June 2016) - Lu, Zeguang; Tang, Tong; Zhou, Ge; Jia, Wanda; Wang, Meng; Xu, Jing; Bai, Shihong
Highlights: Surface gloss is increasing with the increasing air temperature and relative humidity and the decreasing air velocity. Surface gloss is highly affected by the relative humidity. Significantly different amount of surface gloss is 2.2% and above, and highly significant different amount is 5.0% and above. Abstract: One component waterborne wood top coating is dried by dehumidification drying method. An orthogonal experimental design is used to investigate the effect of the air temperature, relative humidity, and air velocity on the surface gloss. The Duncan's multiple range tests are used to analyze the difference between the means of a set of observations. Surface gloss increases as the air temperature and the relative humidity increase, whereas decreases as the air velocity decreases. Relative humidity has a more significant effect on surface gloss than the air velocity, which has a more significant than the air temperature. The difference in surface glosses is significant when the difference in the means is greater than or equal to 2.2%, and is highly significant when the difference is greater than or equal to 5.0%. The results can be used as practical standards to judge differences of surface gloss in different drying environments.